Sex Differences in Intergenerational Income Transmission and Educational Attainment: Testing the Trivers-Willard Hypothesis - Pink, Katharina E.; Schaman, Anna; Fieder, Martin (Frontiers in Psychology, 2017)
From an evolutionary point of view, sex differences in intergenerational transmission of income may be influenced by the Trivers-Willard (T-W) effect: Low status parents should invest more in daughters, whereas high status parents are expected to invest more in sons. This bias in parental investment may result in status-dependent sex biased parental support for higher education and educational attainment and should therefore affect the level of intergenerational income transmission for the sons and daughters. We used the data from the Wisconsin Longitudinal Study (WLS) to model the effect of parental financial investment on the child’s income and educational attainment controlling for the number of siblings. The observed sex differences in intergenerational income transmission demonstrate that sons profited more from parental income and education in terms of their own income than daughters. Furthermore we showed that fathers with a high socioeconomic index (SEI) invest more in their sons education in terms of completed years of education and financial support during college. In contrast daughter of low SEI fathers completed more years of education and received more financial support than sons. However the pattern in intergenerational income transmission might be better explained as a product of sociological factors and reproductive trade-offs in later life rather than as a consequence of the T-W effect.